Pengabdian Tim Kukerta UNRI Dalam Membantu Pengelolaan Ketahanan Pangan Melalui Penanaman Melon Dan Semangka Di Desa Muaro Tombang Kuantan Mudik, Kuantan Singingi. - Zafira Hasna; M.Alfarizi Albi; Andika Ramadhani; Erna Fransiska Br. Nasution; Nanda Ichsan; Vivin Triana; Iqsar Alhamzah; Nabila Tri Azzahra; Wah Zura adelia; Mai Reza (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Muaro Tombang Village is one of the villages located in Kuantan Mudik District, Kuantan Singingi Regency, Riau Province. Muaro Tombang village has a plantation area of ​​50 ha with the average community doing farming and gardening as a job. In the system of social institutions, Muaro Tombang Village has 3 farmer groups. In the field of agriculture and plantations that can be developed is the use of vacant land in the Muaro Tombang area because there is still vacant land that has not been utilized properly. In line with the program being carried out by Muaro Tombang Village, from this vacant land that has not been utilized properly, namely by managing it into land for planting various types of melons and watermelons for food security and improving the economy for the people of Muaro Tombang Village.